Risk factors of perioperative complications and transfusion following total hip arthroplasty in systemic lupus erythematosus patients. (August 2019) - Li, Z; Du, Y; Xiang, S; Feng, B; Bian, Y; Qian, W; Jin, J; Lin, J; Weng, X
Background: In recent years, hip arthroplasty rates in systemic lupus erythematosus (SLE) patients have been increasing rapidly. Although patients with SLE generally show beneficial or desirable functional outcomes following total hip arthroplasty (THA), it has been reported that SLE patients after THA have increased risk of postoperative complications, especially during the period of hospitalization. Objectives: In the present study, we aimed to identify possible factors associated with complications or transfusion of THA in SLE patients during hospitalization. Methods: The present study was a retrospective study conducted in Peking Union Medical College Hospital. Data were collected from medical records of patients who underwent THA from January 2012 to June 2018. The primary outcome variable was perioperative complications, which was defined as having one or more of the following conditions: high fever, infection, impaired wound healing, venous thrombosis of the lower extremities, hematoma, arrhythmia, implant complications. The secondary outcome was perioperative transfusion. Results: During January 2012 to June 2018, 100 patients had taken the surgery of THA. After multivariate analysis, independent risk factors for perioperative complications were: age ≥ 45 years ( p = 0.001), SLE with other connective tissue diseases ( p = 0.029), high temperature ( p = 0.030), positive anti-dsDNA antibody ( p = 0.043), and Systemic Lupus International Collaborative Clinics/American College of Rheumatology (SLICC/ACR) Damage Index ≥ 3 ( p = 0.008). Independent risk factors for perioperative transfusion were bilateral THA ( p = 0.029), low hemoglobin ( p = 0.021) and abnormal renal function ( p = 0.021). Conclusion: For SLE patients following THA, age > 45 years, SLE with other connective tissue disease, high temperature, positive anti-dsDNA antibody and SLICC/ACR Damage Index ≥ 3 were the risk factors of complications during hospitalization and bilateral THA, low hemoglobin and abnormal renal function were the risk factors of transfusion.